Factors associated with the research efficiency of clinical specialties in a research-oriented hospital in China - Li, Yin; Li, Jiachang; Li, Baihong; Cao, Yue; Liu, Menghan; Zhang, Longhao; Zeng, Zhi (PloS one, 2021)
Research-oriented hospitals are responsible for medical services tasks, medical education, and scientific research, playing an important role in medical research and application. The research efficiency of a clinical specialty is influenced by factors such as the characteristics of the specialty, the organizational atmosphere, and the clinical director’s leadership. The present study aimed to describe the research efficiency of clinical specialties, explore the factors influencing it, and clarify the argument of co-evolution theory regarding the collaborative development of medical services, education, and research. Logistic regression and multiple linear regression were adopted to estimate the correlation between influencing factors and scientific research efficiency. Hospital H, which is representative of research hospitals in China, was taken as an example. Taking three efficiency values—comprehensive technical efficiency (CTE), pure technical efficiency (PTE), and scale efficiency (SE)—as dependent variables, the independent variables affecting research productivity were statistically analyzed. This study also examined the scientific research efficiency of 41 specialties between 2013 and 2017, and found that the independent variables affected CTE, PTE, and SE to various degrees. Collaborative innovation in medical education and research must be based on clinical research; how to balance medical and teaching quality, and research efficiency requires further discussion. While young people play a major role on the research team because of their creativity and initiatives, which improve CTE and PTE, high-level researchers with better research and leadership abilities lead to the rational allocation and effective utilization of resources, thus improving SE. In 2013–2017, discipline construction focused on scale expansion, resulting in the decline of SE in China. Therefore, this study suggests further improvements for the efficiency of clinical specialties in research hospitals.